India and nuclear Asia : forces, doctrine, and dangers - Joshi, Yogesh (International relations specialist); O'Donnell, Frank, 1985- (South Asia in world affairs series, 2019)
India's nuclear profile, doctrine, and practices have evolved rapidly since the country's nuclear breakout in 1998. However, the outside world's understanding of India's doctrinal debates, forward-looking strategy, and technical developments are still two decades behind the present. This book will fill that gap in our knowledge by focusing on the post-1998 evolution of Indian nuclear thought, its arsenal, the triangular rivalry with Pakistan and China, and New Delhi's nonproliferation policy approaches. Joshi and O'Donnell show how India's nuclear trajectory has evolved in response to domestic, regional, and global drivers. The book argues that doctrinal and posturing developments in India, China, and Pakistan are elevating inadvertent and accidental escalation risks. As nuclear South Asia continues to attract global concern, this book provides an indispensable and timely guide to its challenges and offers potential solutions to them. Based on primary-source research and interviews, this book will be important reading for scholars and students of India's international relations and security as well as for military, defense contractor, and policy audiences outside of India.